Cognitive-semantic analysis of the meanings of words and phrases in English and Uzbek and their translation problems - Muratkhodjaeva F.X (Periodica Journal, 2022)
In this article, the cognitive-semantic analysis of the meanings of words and phrases in English and Uzbek and their translation problems, the problem of secondary predication in the theoretical grammar of English, the structure of a fragmented sentence in English, the predicative in English It describes in detail the parts of speech that are separated in the classification of their compounds and their role as a syntactic device
Keywords: cognitive-semantic analysis; predicative phrase